Restructuring higher education: Toward a student-led model - Young-sun Koh (Korea Development Institute (KDI), 2023)
A dwindling school-age population is expected to place many universities under greater financial distress in the coming decades. The Ministry of Education's strategy of assessing universities and coercing poorly performing ones to reduce enrollment has proved inadequate to speed up the restructuring process. A fundamental solution should be found in letting students, rather than the Ministry, lead this process by providing them with more and better information on individual universities and departments. For instance, the average salaries of graduates should be made public. It will facilitate 'voting by feet' by students and force universities to focus their efforts on enhancing their core competencies. It has additional advantages in protecting the restructuring process from political interference, enabling a better matching between supply and demand of skills, and promoting the autonomy in higher education.
Keywords: 330